Estudo Experimental do Escoamento Atmosférico ao Redor de um Obstáculo Isolado na Camada Limite Atmosférica - de Paula, Reginaldo R. C.; Gomes, Marcos S. P.; Demuner, Juan C. D.; Ricardo, Ana L. S.; Pereira, Karina S. (Ciência e Natura, 2011)
.